Pelatihan Peningkatan Kompetensi Guru Menggunakan Media Pembelajaran Jarak Jauh Menggunakan Google Classroom, Zoom, dan Google Meet di SMAN 1 Teluk Sebong Bintan - Sara, Michelle Firsta Karima; Zakaria, Zakaria (Jurnal Vokasi Teknik Informatika, 2022)
The government's approach to preventing the spread of the COVID-19 virus is to establish social distance. According to observations, teachers at SMAN 1 Teluk Sebong are still quite inexperienced in managing online learning during the COVID-19 epidemic. The goal of this research was to increase teacher competency in utilizing the Google Classroom, Zoom, and Google Meet application media. The advantage of research is that it may expand knowledge in the field of education, particularly in increasing abilities using the Google Classroom, Zoom, and Google Meet applications as reference material for every instructor in carrying out the learning process. Methods This study employs an R & D (Research and Development) research paradigm based on the ADDIE model. According to the findings of this study, school-based training might increase teacher competency in the online teaching and learning process throughout the pandemic. This is based on data from pretest and posttest findings, as well as the training process used by schools to increase instructors' professional abilities in the online teaching and learning process. The average pretest score is 1.62, while the average posttest score is 3.14. It was decided that the training offered at SMAN 1 Teluk Sebong benefited instructors by strengthening their professional competence in the online teaching process. Continual and continuous training gives instructors an excellent opportunity to expand their knowledge and develop their abilities.